Atrial Fibrillation in the 21st Century: A Current Understanding of Risk Factors and Primary Prevention Strategies - Menezes, Arthur R.; Lavie, Carl J.; DiNicolantonio, James J.; O'Keefe, James; Morin, Daniel P.; Khatib, Sammy; Milani, Richard V. (Mayo Clinic proceedings, 2013)
Atrial fibrillation (AF) is the most common arrhythmia worldwide, and it has a significant effect on morbidity and mortality. It is a significant risk factor for stroke and peripheral embolization, and it has an effect on cardiac function. Despite widespread interest and extensive research on this topic, our understanding of the etiology and pathogenesis of this disease process is still incomplete. As a result, there are no set primary preventive strategies in place apart from general cardiology risk factor prevention goals. It seems intuitive that a better understanding of the risk factors for AF would better prepare medical professionals to initially prevent or subsequently treat these patients. In this article, we discuss widely established risk factors for AF and explore newer risk factors currently being investigated that may have implications in the primary prevention of AF. For this review, we conducted a search of PubMed and used the following search terms (or a combination of terms): atrial fibrillation, metabolic syndrome, obesity, dyslipidemia, hypertension, type 2 diabetes mellitus, omega-3 fatty acids, vitamin D, exercise toxicity, alcohol abuse, and treatment. We also used additional articles that were identified from the bibliographies of the retrieved articles to examine the published evidence for the risk factors of AF.